SISTEM USULAN PUBLIK OPERASIONAL DAN PEMELIHARAAN KOTA PALANGKA RAYA BERBASIS ANDROID - Hermawan Hasibuan , Liyando; kusbianto, maruf (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
Information technology is very important part. With existing innovations, information technology can provide convenience in many ways. Public facility, transportation, communication, social, economic and many other things has been influenced by information technology.Part of the technology is growing rapidly making some breakthroughs especially in terms of providing reports. Unlike manual reports which should be written in a certain format for easy work. Reports with the use of information technology seem more flexible with better capacity.That way, Smartphone Reports help can contribute using the use of information technology, Reports shift toward easier, cheaper, and faster. Public proposals to governments should also follow the influence of the times, Reports are expected to be easily accessible for rapid processing by society. So that in terms of utilization is expected to have a better added value.The existence of this application also proves the speed of Information Technology so that it can be useful as a means of life support. Where everyone will feel the benefits especially in Palangka Raya that has quite enough population. With so many public facilities that may have a lot of damage to this application will be easily appointed as a form of reporting.It is expected that with this application not only help the public but also facilitate the work of the relevant agencies.